PERAN GURU DALAM PENGELOLAAN KELAS MEMOTIVASI TINGKAT BELAJAR PESERTA DIDIK SMAK SINT CAROLUS KUPANG - Taek , Emilia Dolorosa; Un Bria , Florens Maxi; Meno, Dionoesia (STIPAS Keuskupan Agung Kupang, 2022)
The teacher's role in managing the class is motivation for students to increase students' desire to learn. An active and creative teacher will make the class come alive and give students their own color in learning. The focus of this research is to examine student success which is not only determined by the students' abilities but also depends on the role and abilities of a class teacher who actively and creatively encourages students to study more actively. The research method used is a qualitative method, with a descriptive model research approach. In accordance with the initial data obtained, it was found that at SMAK Sint Carolus Boromeus Kupang, one of the causes of teachers not managing their classes well was their lack of mastery of technology and only using monotonous teaching methods and a lack of good interaction with students. This makes students feel bored, unfocused and less active in participating in learning and students lack motivation in learning. The results obtained from this research are that teachers have played a very good role in classroom management, only efforts need to be made by the school to help teachers use more creative learning technology.